2012
DOI: 10.1111/apt.12115
|View full text |Cite
|
Sign up to set email alerts
|

Use of systemic glucocorticoids and the risk of colorectal cancer

Abstract: SUMMARY BackgroundSystemic glucocorticoids are potent immunosuppressants, potentially facilitating carcinogenesis. Studies examining glucocorticoids and colorectal cancer risk are few.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We excluded patients who developed malignancy before CST administration in the evaluation between malignancy and CST. The following eight variables were evaluated in 68 patients receiving CST during follow-up: (1) period of CST (<6 versus >6 months), (2) period of CST (<3 versus >3 years), (3) CST without cessation from diagnosis, (4) cumulative period of CST until development of malignancy, (5) cumulative amount of CST until development of malignancy, (6) cumulative period of CST during follow-up, (7) cumulative amount of CST during follow-up and (8) follow-up period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded patients who developed malignancy before CST administration in the evaluation between malignancy and CST. The following eight variables were evaluated in 68 patients receiving CST during follow-up: (1) period of CST (<6 versus >6 months), (2) period of CST (<3 versus >3 years), (3) CST without cessation from diagnosis, (4) cumulative period of CST until development of malignancy, (5) cumulative amount of CST until development of malignancy, (6) cumulative period of CST during follow-up, (7) cumulative amount of CST during follow-up and (8) follow-up period.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has not been clarified whether patients with IgG4-RD are at high risk for developing a malignancy. CST is a risk factor to develop malignancy [7][8][9][10][11][12]. The associations between CST and malignancies in the IgG4-RD or AIP populations have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…This case-controlled study suggested that not only aspirin but also other drugs may be effective chemopreventative agents for colorectal cancer. Some drugs, such as Ca-channel blockers and steroids, had no such effect in previous studies (32,39,40). As these previous studies were retrospective analyses, they could have been affected by bias.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, only 7 patients received calcium by prescription and it was not significantly associated with colorectal cancer prevention. Many of the remaining hits in this study have been previously assessed for colorectal cancer preventative effects, including vitamin B, vitamin C, vitamin E, folic acid, bisphosphonates, Ca-channel blockers, ARB, thienopyridine, nitrovasodilators, probiotics, statins, and steroids (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Vitamin B, vitamin C, vitamin E, folic acid, bisphosphonates, and probiotics may have some colorectal cancer preventive effects, although the evidence is not yet strong.…”
Section: Discussionmentioning
confidence: 99%
“…It may occur sporadically or in association with neurofibromatosis type 2 (NF2) [2]. Approximately 120 cases of MA have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%